2016
DOI: 10.1109/tap.2016.2565682
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a High-Gain 60-GHz Corrugated Slot Antenna Array With Ridge Gap Waveguide Distribution Layer

Abstract:  Abstract-A wideband, high gain high efficiency 16×16-element slot antenna array is presented for 60 GHz band applications. The antenna is designed based on gap waveguide technology. The most important advantage of using this technology is its ability to decrease complexity and cost of fabrication because there is no requirement of electrical contact between the three layers of the antenna structure. The three layers are a corrugated metal plate with radiating slots, a sub-array cavity layer, and a ridge gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 33 publications
0
72
0
Order By: Relevance
“…At high frequencies, due to small wavelength and dimensions, fabrication tolerances and good electrical contact requirements, the fabrication process of conventional waveguide components is a challenge. Gap waveguide technology is a newly developed technology based on soft and hard surfaces which has been used in many conventional microwave components . This technology overcomes the problem of good electrical contact associated with mechanical assembly especially at high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…At high frequencies, due to small wavelength and dimensions, fabrication tolerances and good electrical contact requirements, the fabrication process of conventional waveguide components is a challenge. Gap waveguide technology is a newly developed technology based on soft and hard surfaces which has been used in many conventional microwave components . This technology overcomes the problem of good electrical contact associated with mechanical assembly especially at high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…RGW characterizes its simple mechanical assembly, low losses, wider bandwidth compared to rectangular waveguide. Many applications in gap waveguide technology such as power divider, filter, coupler, and slot antenna have been realized [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…2.19. Besides, in [75] it is also demonstrated that the coupling is lower than −20 dB in case of one row of nails, lower than -37 dB using two rows of nails and -50 dB for three rows of nails in the desired frequency band (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68).…”
Section: Rgw Corporate-feed Networkmentioning
confidence: 95%
“…Practically all their proposals consist of multilayer linearly-polarized antennas composed by several unconnected layers, thanks to the properties of the Gap Waveguide technology. Notable contributions for their simplicity and performance can be found in [68]- [67]. There are much more examples of high-gain linear-polarized antennas in the mm-wave band [76]- [79], but they are not completely metallic since they make use of SIW or LTCC.…”
Section: Satcommentioning
confidence: 99%
See 1 more Smart Citation